Combination of cisplatin and bromelain exerts synergistic cytotoxic effects against breast cancer cell line MDA-MB-231 in vitro. Issue 1 (December 2016) - Pauzi, Ahmad; Yeap, Swee; Abu, Nadiah; Lim, Kian; Omar, Abdul; Aziz, Suraini; Chow, Adam; Subramani, Tamilselvan; Tan, Soon; Alitheen, Noorjahan
Abstract Background Bromelain, which is a cysteine endopeptidase commonly found in pineapple stems, has been investigated as a potential anti-cancer agent for the treatment of breast cancer. However, information pertaining to the effects of combining bromelain with existing chemotherapeutic drugs remains scarce. This study aimed to investigate the possible synergistic cytotoxic effects of using bromelain in combination with cisplatin on MDA-MB-231 human breast cancer cells. Method MDA-MB-231 cells were treated with different concentrations (0.24–9.5 µM) of bromelain or cisplatin alone, as well as four different combinations of these two agents to assess their individual and combination effects after 24 and 48 h. Cell viability was analyzed using an MTT assay. The induction of apoptosis was assessed using cell cycle analysis and an Annexin V-FITC assay. The role of the mitochondrial membrane potential in the apoptotic process was assessed using a JC-1 staining assay. Apoptotic protein levels were assessed by western blot analysis and proteome profiling using an antibody array kit. Results Single-agent treatment with cisplatin or bromelain led to dose- and time-dependent decreases in the viability of the MDA-MB-231 cells at 24 and 48 h. Furthermore, most of the combinations evaluated in this study displayed synergistic effects against MDA-MB-231 cells at 48 h, with combination 1 (bromelain 2 µM + cisplatin 1.5 µM) exhibiting the greatest synergistic effect (P  = 0.000). The results of subsequent assays indicated that combination 1 treatment induced apoptosis via mitochondria-mediated pathway. Combination 1 also resulted in significant decreases in the levels of several apoptotic proteins such as Bcl-x and HSP70, compared with bromelain (P  = 0.002 and 0.000, respectively) or cisplatin (P  = 0.000 and 0.001, respectively) single treatment. Notably, MDA-MB-231 cells treated with combination 1 showed increased levels of the pro-apoptotic proteins Bax compared with those treated with bromelain (P  = 0.000) or cisplatin single treatment (P  = 0.043). Conclusion Bromelain in combination with cisplatin synergistically enhanced the induction of apoptosis in MDA-MB-231 cells.